PERDAGANGAN INTERNASIONAL PERSPEKTIF ISLAM; : STUDI KASUS: DILEMA PENGEMBANGAN EKPOR RUMPUT LAUT DI KABUPATEN BULUKUMBA - Kaslam, Kaslam (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2022)
Trade is one aspect of muamalah in Islam. This case gets special attention in Islamic economics because buying and selling must comply with the provisions outlined by religion so that it can be of worship value, one example is the practice of international trade. International trade is an activity of exchanging goods, services or other factors of production across national borders. South Sulawesi has a number of superior commodities that are exported to other countries, one example is seaweed from Bukulumba Regency. However, the problem that occurs is that demand is very high but not directly proportional to the welfare of farmers. This article aims to get to the root of the problem and offer a solution. The method used is descriptive qualitative with a survey approach. The result is that based on Islam in carrying out any trading activities, each party should benefit from each other. The two verses on which it is based are Surah An Nisa ': 29 and Surah Al Baqarah: 275. These two verses explain that in trading, it should be based on mutual pleasure and not eating each other's property in a vanity way and prohibiting the practice of usury. The other solution approach is sustainable community empowerment to process seaweed in the form of finished products, so that it has a competitive price compared to selling it in raw form.